Quantifying gender disparity in physician authorship among commentary articles in three high-impact medical journals: an observational study - Mamtani, Mira (BMJ Open, 2020)
BACKGROUND: Scholarship plays a direct role in career advancement, promotion and authoritative recognition, and women physicians remain under-represented as authors of original research articles. OBJECTIVE: We sought to determine if women physician authors are similarly under-represented in commentary articles within high-impact journals. DESIGN/SETTING/PARTICIPANTS: In this observational study, we abstracted and analysed author information (gender and degree) and authorship position from commentary articles published in three high-impact journals between 1 January 2014 and 16 October 2018. PRIMARY OUTCOME MEASURE: Authorship rate of commentary articles over a 5-year period by gender, degree, authorship position and journal. SECONDARY OUTCOME MEASURES: To compare the proportion of men and women physician authorship of commentaries relative to the proportion of men and women physician faculty within academic medicine; and to examine the gender concordance among the last and first authors in articles with more than one author. RESULTS: Of the 2087 articles during the study period, 48% were men physician first authors compared with 17% women physician first authors (p<0.0001). Of the 1477 articles with more than one author, similar distributions were found with regard to last authors: 55% were men physicians compared with only 12% women physicians (p<0.0001). The proportion of women physician first authors increased over time; however, the proportion of women physician last authors remained stagnant. Women coauthored with women in the first and last authorship positions in 9% of articles. In contrast, women coauthored with men in the first and last author positions, respectively, in 55% of articles. CONCLUSIONS: Women physician authors remain under-represented in commentary articles compared with men physician authors in the first and last author positions. Women also coauthored commentaries with other women in far fewer numbers.